Influence of High-speed Railway to Power Quality and its Governance Measures - 周方圆; 王卫安 (Kongzhi Yu Xinxi Jishu)
The principles of traction power supply and the load characteristics are described briefly for high-speed railway. The power quality problems such as negative sequence and harmonic on the power supply system caused by high-speed railway are analyzed. Then, the existing measures of domestic and overseas power quality management for high-speed railway are introduced. Last, the new ideas and new measures for high-speed railway power quality control are proposed.